Cash incentives to spur Kedah athletes - Noh, Dasheer (The Star, 2013)
TO lift the morale of Kedah athletes who are currently participating in the 16th Malaysia Games in Kuala Lumpur, Menteri Besar Datuk Mukhriz Mahathir announced cash incentives of RM3,000, RM2,000 and RM1,000 for gold, silver and bronze medal winners respectively.